SPE Energy Resources Conference 2014
DOI: 10.2118/169936-ms
|View full text |Cite
|
Sign up to set email alerts
|

Successful Single-Stage Cementing in a Weak Formation: A Case History in Spain

Abstract: Cementing in wellbores with low fracture gradients can be challenging due to the risk of formation breakdowns when exceeding maximum allowable equivalent circulation densities (ECDs). Consequences include severe losses and formation damage, and insufficient placement of the cement slurry that necessitates time-consuming and costly remedial cementing to ensure zonal isolation.In recent cementing operations in Spain, the formation integrity test (FIT) of the open hole section indicated that the formation would h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 7 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…The successful application and the mechanism of the sealing spacer fluid containing membrane forming colloids have been described in previous studies (Metcalf et al 2011, Budiawa et al 2014. Bottiglieri et al 2014 reported that the sealing spacer increased the frac initiation and propagation pressure in formations based on a case history. The main component of this fluid system is a hydrophobically modified polymer.…”
Section: Sealing Spacer Fluidmentioning
confidence: 99%
“…The successful application and the mechanism of the sealing spacer fluid containing membrane forming colloids have been described in previous studies (Metcalf et al 2011, Budiawa et al 2014. Bottiglieri et al 2014 reported that the sealing spacer increased the frac initiation and propagation pressure in formations based on a case history. The main component of this fluid system is a hydrophobically modified polymer.…”
Section: Sealing Spacer Fluidmentioning
confidence: 99%